INTEGRATED MODEL OF AUTOMATED PROCESS LIFECYCLE MANAGEMENT TRAINING THROUGH STRUCTURIZATION CONTENT OF HIGH SCHOOL AND ORGANIZATIONS - Gennady G. Kulikov; Vyacheslav V. Antonov; Maria A. Shilina; Almira R. Fahrullina (Статистика и экономика, 2016)
This article discusses the modern point of view, the issue of developing methods of forming the structure of the process lifecycle management of specialisttraining in conjunction with the University of industrial enterprise on the basisof a comprehensive content base chair. The possibility of using IT to improve the efﬁciency of educational processes.